Baranek – Lew z pokolenia Judy Chrystocentryczna reinterpretacja Rdz 49,9 w Ap 5,5 - Karczewski, Marek (Biblica et Patristica Thoruniensia, 2011)
The title of presentation – Lamb – Lion of tribe of Judah. A christocentric reinterpretation of Gen 49,9 in Rev 5,5 suggests the object of study – the intertextuality of biblical texts of Gen and Rev. In the methodological part we find questions of methodological problems in the theological contact between Rev – Gen. In the second part we study problem of reinterpretation Gen 49,9 in Rev 5,5. During the analysis sought to take account of the original character of the theological texts in Genesis Book, so its essential scheme is based on three points; the first- an analysis of the text of Gen 49,9. The second is to determine the context of the text in Rev 5,5 and is an attempt to theological interpretation, with particular emphasis on the intensity and contrast, or allusion to the continuation of the content of the Genesis Book. The last steep is interpretation of title “Lion of tribe of Judah” on the light of the Christology of Rev.